Protein Expression of TXNIP in the Dopaminergic Neurons of Subjects with Parkinson’s Disease: Evidence from a Pilot Study - Schillaci, Francesca A.; Lanza, Giuseppe; Salluzzo, Maria Grazia; Ferri, Raffaele; Salemi, Michele (Life (Basel, Switzerland), 2025)
Parkinson’s disease (PD) is a progressive, multisystemic α-synucleinopathy, recognized as the second most prevalent neurodegenerative disorder globally. Its neuropathology is characterized by the degeneration of dopaminergic neurons, particularly in the substantia nigra pars compacta (SNpc), and the intraneuronal accumulation of α-synuclein-forming Lewy bodies. Oxidative stress is a key contributor to PD pathogenesis. Thioredoxin-interacting protein (TXNIP) is a crucial regulator of cellular redox balance, inhibiting the antioxidant function of thioredoxin. This pilot study aimed to investigate the protein expression and localization of TXNIP in the SNpc of PD patients compared to healthy controls. We performed immunohistochemical analyses on 12 post-mortem human brain sections (formalin-fixed, paraffin-embedded) from six subjects with PD and six healthy controls. The study was performed on PD subjects with Braak stage 6. Our findings revealed that in control samples, TXNIP protein was distinctly and closely associated with neuromelanin (NM) pigment within the cytoplasm of SNpc dopaminergic neurons. Conversely, in PD samples, there was a markedly weak cytoplasmic expression of TXNIP, and critically, this association with NM pigment was absent. Furthermore, PD samples exhibited a significant reduction in both dopaminergic neurons and NM content, consistent with advanced disease. These findings, which mirror previous transcriptomic data showing TXNIP gene under-expression in the same subjects, suggest that altered TXNIP expression and localization in SNpc dopaminergic neurons are features of late-stage PD, potentially reflecting neuronal dysfunction and loss.